1986
DOI: 10.1073/pnas.83.4.1145
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid sensitivity of vasopressin mRNA levels in the paraventricular nucleus of the rat.

Abstract: Immunocytochemical studies have shown that adrenalectomy produces changes in the content and distribution of [arginine-8]vasopressin (AVP) immunoreactivity in the paraventricular nucleus of the hypothalamus. The purpose of this study was to determine whether manipulation of adrenal hormones affects the levels of AVP mRNA. In situ hybridization assays with highly specific synthetic oligodeoxyribonucleotide probes and immunocytochemistry were used to detect the distribution of AVP mRNA and AVP-immunoreactive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(72 citation statements)
references
References 34 publications
6
65
0
1
Order By: Relevance
“…This sequence element overlaps partially with an ERE of the oxytocin gene -91 to -72) suggesting that positively and negatively acting protein factors may be involved in the expression of this gene. Similar potential regulatory sequence elements can be found in the Table 1 The putative promoter region of the rat oxytocin gene contains several potential gincocorticoid (GRE)-and estrogen-responsive elements (ERE) upstream of the transcription start site promoter region of the vasopressin gene (Mohr, E., unpublished) which agrees with the finding that upregulation of one gene concomitantly affects expression of the other [1][2][3][4][5][6][7][8].…”
Section: Biotinylated Probesupporting
confidence: 71%
See 1 more Smart Citation
“…This sequence element overlaps partially with an ERE of the oxytocin gene -91 to -72) suggesting that positively and negatively acting protein factors may be involved in the expression of this gene. Similar potential regulatory sequence elements can be found in the Table 1 The putative promoter region of the rat oxytocin gene contains several potential gincocorticoid (GRE)-and estrogen-responsive elements (ERE) upstream of the transcription start site promoter region of the vasopressin gene (Mohr, E., unpublished) which agrees with the finding that upregulation of one gene concomitantly affects expression of the other [1][2][3][4][5][6][7][8].…”
Section: Biotinylated Probesupporting
confidence: 71%
“…Conversely the two genes appear to be downregulated when rats are exposed to excess of serum vasopressin [2]. Another regulatory mechanism has been observed in certain cell types of the hypothalamo-pituitary axis where expression of the vasopressin gene is negatively controlled by steroids [3][4][5][6]. Upregulation of the oxytocin gene has been observed in female rats during pregnancy and lactation [7,8] and in analogy to the Correspondence address: D. Richter, Institut fiir Zeilbiochemie und klinisch¢ Neurobiologie, Universit~its-Krankenhaus Eppendorf, Martinistr.…”
Section: Introductionmentioning
confidence: 99%
“…The change in AVP synthesis was reversible by pretreatment with dexamethasone or corticosterone (Silverman et al, 1981;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991). The effect of stressful stimuli on the synthesis of CRH and AVP in the PVN does not parallel the findings with high levels of exogenously applied corticosteroids.…”
Section: Peptidesmentioning
confidence: 75%
“…Following ADX, CRH synthesizing parvocellular neurons start to produce AVP (Silverman et al, 1981;Tramu et al, 1983;Kiss et al, 1984;Sawchenko et al, 1984;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991). The change in AVP synthesis was reversible by pretreatment with dexamethasone or corticosterone (Silverman et al, 1981;Davis et al, 1986;Swanson and Simmonds, 1989;Imaki et al, 1991).…”
Section: Peptidesmentioning
confidence: 99%
“…Adrenalectomy markedly increases the levels of CRH and AVP immunoreactivity (Antoni et al 1983, Paull & Gibbs 1983, Kiss et al 1984, and the amount of mRNA transcripts of CRH and AVP gene (Wolfson et al 1985, Antoni 1986, Davis et al 1986 in the neurons of the PVN which contains glucocorticoid receptors in rats (Reul & De Kloet 1985). It has also been reported that adrenalectomy increases the concentration of CRH and AVP in hypophysial portal blood (Oliver et al 1983, Kooy et al 1990) and the median eminence (Suda et al 1983, Holmes et al 1986).…”
Section: Figurementioning
confidence: 99%